Legal Controls for Expropriation Procedures in Libyan Law (Al-Farooq Journal of Sciences, 2026)
The expropriation of private property for public utility in Libya is an exceptional administrative procedure that compulsorily divests a citizen of their real estate for public projects strictly conditional upon fair prior compensation based on current market values. Historically this concept shifted from the protective 1961 Royal Decree-Law to a socialist totalitarian phase (1978-2011) under restrictive laws like Law No 4 of 1978 which confiscated private holdings before finally entering a recovery  phase though Laws No 16 and 20 of 2015 that repealed previous statutes and activated modern restitution and valuation committees.Structurally, the process unfolds in sequential stages: it begins with a Cabinet decree declaring public utility, followed by a 30 day public inventory and cadastral survey to review objections, moves to financial valuation by specialized committees, and resolves either amicably via settlement or compulsorily by depositing the funds into the court treasury, concluding with the official title transfer under the States name at the Real Estate Registration Authority.
Keywords: Public Utility Fair Compensation